Metaphorical Language Innovation in the Globalization Context - Oktavianus, Oktavianus; Ferdinal, Ferdinal; Pratiwi, Desak Putu Eka; Utami, Ni Putu Cahyani Putri (Humanus, 2024)
Metaphorical language innovation, which originates from thought processes and interactions between fellow language speakers and with the natural surroundings, leads to various configurations of lingual forms. Therefore, this study investigated the linguistic innovations to create metaphorical expression, its role in decorating text, and the effect of globalization on metaphor in daily life. The data for this study were metaphorical languages in daily life, social and online media. This research applied a qualitative approach and the concept and theory of metaphor. The data were collected using participant and non-participatory observation methods. The data were analyzed using the Intra-Lingual Referential Method and the Extra-Lingual Referential Method or the Distributional and Referential Method, using the techniques of relating and comparing the elements of language related to metaphor as the research object. The results of data analysis showed that the analogy of target and source domain gives rise to simple and complex metaphors. Metaphors have an essential role in building the beauty of a text. Metaphors decorate a text and stimulate the reader's imagination when reading literary works. Besides, globalization distributes, enriches, and colors the metaphors in a language